Diagnostic value of the cardiac electrical biomarker, a novel ECG marker indicating myocardial injury, in patients with symptoms suggestive of non‐ST‐elevation myocardial infarction. Issue 4 (24th February 2018) - Strebel, Ivo; Twerenbold, Raphael; Boeddinghaus, Jasper; Abächerli, Roger; Rubini Giménez, Maria; Wildi, Karin; Grimm, Karin; Puelacher, Christian; Badertscher, Patrick; Sabti, Zaid; Breitenbücher, Dominik; Jann, Janina; et al.
Abstract : Background: The cardiac electrical biomarker (CEB) is a novel electrocardiographic (ECG) marker quantifying the dipolar activity of the heart with higher levels indicating myocardial injury. Methods: We prospectively enrolled 1097 patients presenting with suspected non‐ST‐elevation myocardial infarction (NSTEMI) to the emergency department (ED). Digital 12‐lead ECGs were recorded at presentation and the CEB values were calculated in a blinded fashion. The final diagnosis was adjudicated by two independent cardiologists. The prognostic endpoint was all‐cause mortality during 2 years of follow‐up. Results: NSTEMI was the final diagnosis in 14% of patients. CEB levels were higher in patients with NSTEMI compared to other causes of chest pain (median 44 (IQR 21–98) vs. 30 (IQR 16–61), p  < .001). A weak but significant correlation between levels of high‐sensitivity cardiac troponin T (hs‐cTnT) at admission to the ED and the CEB was found ( r  = .23, p  < .001). The use of the CEB in addition to conventional ECG criteria improved the diagnostic accuracy for the diagnosis of NSTEMI as quantified by the area under the receiver operating characteristics curve from 0.66 to 0.71 ( p  < .001) and the sensitivity improved from 43% to 79% ( p  < .001). Conclusion: In conclusion, the CEB, an ECG marker of myocardial injury, significantly improves the accuracy and sensitivity of the ECG for the diagnosis of NSTEMI.